Authority and Control in the Countryside From Antiquity to Islam in the Mediterranean and Near East (6th-10th Century) - Delattre, Alain; Legendre, Marie; Sijpesteijn, Petra (Leiden Studies in Islam and Society, 2018)
Authority and Control in the Countryside looks at the economic, religious, political and cultural instruments that local and regional powers in the late antique to early medieval Mediterranean and Near East used to manage their rural hinterlands.; Readership: All interested in the history of the late antique and medieval Mediterranean and Near East. Students and scholars of economic, social, political and cultural history, archaeology, papyrology, numismatics, philology, religious studies from the Iberian Peninsula and the Balkan to Arabia and Central Asia in the Roman, Sasanian and Islamic period.